Cross‐cultural validation of the Turkish version of SCORE‐15. Issue 2 (30th July 2021) - Işık, Erkan; Günsel, Damla Ayşegül; Stratton, Peter
Abstract: The purpose of the current study was to examine the validity and reliability of the fifteen‐item Systemic Clinical Outcome and Routine Evaluation (SCORE‐15) Turkish version. The suggested three‐factor structure was confirmed with a total sample of 327 participants including both community and clinical samples. The results of factorial invariance tests demonstrated that the structure of the scale was consistent across both gender and community/clinical groups. Furthermore, discriminant validity was supported by negative correlations with marital satisfaction, life satisfaction and general family functioning as lower scores in SCORE‐15 reflect better adjustment. Furthermore, results showed that SCORE‐15 has good internal consistency reliability and significantly differentiates between community and clinical samples. Overall, these findings indicate that the Turkish version of SCORE‐15 is a valid and reliable instrument that can be used for assessing family functioning in routine clinical practice and family therapy research. Practitioner points SCORE‐15 is a brief and effective instrument for assessing overall family functioning with specific dimensions of family strengths, communication and difficulties The Turkish version of SCORE‐15 exhibited similar factorial properties across gender and community/clinical groups The Turkish version of SCORE‐15 can be used in both clinical and community contexts for research and intervention